Penyuluhan Interaksi Obat dengan Nutrien sebagai Upaya Peningkatan Kesadaran Kesehatan Masyarakat Gadingkembar - Mukti, Taufiq Satria; Firdaus, Muhammad Rizqi Mudhoffar; Fiatun, Ida; Amanda, Citra Salasa; Noviafitri, Kartika Satya (Universitas Muhammadiyah Malang, 2025)
Purpose – Consuming drugs together with food or drink has become a community habit, especially in Gadingkembar. This habit hurts body health for certain conditions as a side effect. Therefore, this outreach aims to increase the health awareness of the Gadingkembar regarding drug interactions with nutrients. Design/methodology/approach– This counseling was carried out using a Community-Based Interactive Approach (CBIA) through the PKK and Gadingkembar Posyandu. This counseling involved health experts from the Jabung Health Center. The population in the activity is the entire community in Gadingkembar. Meanwhile, samples as a result of extension activities were taken randomly from participants who were involved in extension assistance. Extension assistance activities are carried out through three stages, namely Preparation, Implementation, and Evaluation. Findings – The results of counseling assistance activities showed a significant change in public understanding after counseling on drug interactions with nutrients. These results also confirmed through observations of people who were taking medication. It is valid that the community has understood well and in practice, the impact of the extension has been considered successful. Originality/value – This Counseling activity can increase awareness and change the behavior of the Gadingkembar regarding drug interactions with nutrients in the form of food or drinks for better health.